Preparação e caracterização de compósitos magnéticos com potencial para adsorção de fármacos aniônicos e catiônicos - Gomes, Danyelli do Nascimento (2018)
Organic-inorganic polymer composites are materials with considerable potential to use in biomedicine and effluents treatments. The presence of organic groups may be used to adsorb/release drug or pollutants. Moreover, the magnetic properties observed in some inorganic oxides have relevant applicability in separation/transport processes. In the present work, magnetic composites were obtained by interpolyelectrolyte complex method between chitosan and poly (sodium 4-styrenessulfonate)-NaPSS in presence of magnetite nanoparticles. The magnetic composites were obtained with molar ratio rSA (sulfonate/aminium), 0.70. In addition, interpolyelectrolyte complexes with no absence of magnetite were prepared in the same ratios for comparison with magnetic composites. The obtained products were characterized by X-ray diffraction (XDR), Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA) and zeta potential (ζ). The results of FTIR allowed the identification of functional groups present in the obtained materials, proving the presence of magnetite particles in the magnetic composite. From the XRD, it was observed that the magnetite remained unchanged when added to the polymer matrix, maintaining its crystalline phase. In addition, the crystallite size of the magnetic composite comprised in a range of 12-13 nm. Zeta potential values indicated positive surface charges for the composite (MC+). Equilibrium assays were performed to monitor the adsorption process of two drugs, tetracycline and sodium cromoglycate, on the particles of the magnetic composite (MC+). Adsorption isotherms have described this process and the magnetic composites have been shown to be good adsorbents of cationic and anionic drugs.